Powder and method for producing powder
By adding nanotube-shaped particles and magnetic particles to the aluminzinate particles in the powder, the problem of difficult separation of powder in liquid is solved, and the powder is easy to separate and collect under the magnetic field is achieved, and the application efficiency and recycling convenience are improved.
Patent Information
- Application Number
- JP2024138960
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2044-08-20
AI Technical Summary
In the prior art, it is difficult to effectively separate or collect the powder after being dispersed in a liquid, especially when it is used as an adsorbent, solid-liquid separation is required.
It is easy to separate and collect under a magnetic field by adding nanotube-shaped particles and magnetic particles to the aluminzinate particles in the powder.
It realizes easy separation and collection of powder in liquid, improving the application efficiency and convenience of recycling of powder.
Smart Images

Figure 0007656760000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a powder. More specifically, the present invention relates to a powder comprising aluminosilicate granules. The present invention also relates to a method for producing the powder. [Background technology]
[0002] Patent Document 1 discloses a powder containing granules formed by aggregation of halloysite containing halloysite nanotubes. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2018 / 079556 Summary of the Invention [Problem to be solved by the invention]
[0004] When the powder described in Patent Document 1 is dispersed in a liquid for processing, a process for recovering the powder may be further performed after the processing. For example, when the powder is used as an adsorbent for components in a liquid, solid-liquid separation is required to recover the adsorbent (powder) that has adsorbed the components in the liquid. Furthermore, when the powder described in Patent Document 1 is mixed with other powders to form a mixed powder and then processed, a process of recovering the powder from the mixed powder may be further carried out after the processing. Therefore, an object of the present invention is to provide a powder that can be easily separated or recovered. Another object of the present invention is to provide a method for producing the powder. [Means for solving the problem]
[0005] As a result of intensive research into achieving the above-mentioned object, the inventors discovered that when the granules contained in the powder contain nanotube-shaped particles and magnetic particles, separation or recovery operations become easier, and thus completed the present invention.
[0006] That is, the present invention provides the following [1] to
[16] . [1] A powder containing aluminosilicate granules, The aluminosilicate granules include nanotube particles and magnetic particles. [2] The powder according to [1], wherein the magnetic particles are soft magnetic particles. [3] The powder according to [1] or [2], wherein the soft magnetic particles are soft ferrite particles. [4] The powder according to any one of [1] to [3], wherein the content of the magnetic particles is 3 to 30 mass % based on the total mass of the aluminosilicate granules. [5] The powder according to any one of [1] to [4], wherein the aluminosilicate granules have pores having a pore size of more than 8 nm and not more than 200 nm. [6] The powder according to [5], wherein the aluminosilicate granules have, as the pores, first pores derived from the tube pores of the nanotube particles and second pores different from the first pores. [7] The powder according to any one of [1] to [6], wherein the aluminosilicate granules have pores with a pore size of 8 nm or less. [8] The powder according to any one of [1] to [7], wherein the aluminosilicate granules have pores having a pore size of 8 nm or less and pores having a pore size of more than 8 nm and not more than 200 nm. [9] The powder according to any one of [1] to [8], wherein the aluminosilicate granules have pores having a pore size of more than 200 nm.
[10] The powder according to any one of [1] to [9], wherein the aluminosilicate granules have pores having a pore size of more than 8 nm and not more than 200 nm and pores having a pore size of more than 200 nm.
[11] The powder according to any one of [1] to
[10] , wherein the aluminosilicate granules have pores having a pore size of 8 nm or less, pores having a pore size of more than 8 nm and less than 200 nm, and pores having a pore size of more than 200 nm.
[12] The powder according to any one of [1] to
[11] , wherein the aluminosilicate granules have first pores derived from the nanotube particles and having a pore size of more than 8 nm and not more than 200 nm, second pores different from the first pores and having a pore size of more than 8 nm and not more than 200 nm, and third pores having a pore size of 8 nm or less.
[13] The powder according to any one of [1] to
[12] , wherein the nanotube particles are nanotube aluminosilicate particles.
[14] The powder according to
[13] , wherein the nanotube particles include one or more types of particles selected from the group consisting of halloysite nanotube particles, metahalloysite nanotube particles, and modified halloysite nanotube particles.
[15] The powder according to any one of [1] to
[14] , wherein the aluminosilicate granules have an average particle size of 0.5 to 200 μm.
[16] A method for producing the powder according to any one of [1] to
[15] , comprising the step of preparing the powder from a slurry containing nanotube particles and magnetic particles. Effect of the Invention
[0007] According to the present invention, a powder that can be easily separated or recovered can be provided. Furthermore, the present invention can provide a method for producing a powder. [Brief description of the drawings]
[0008] [Figure 1] 1 is an X-ray diffraction chart of a powder of an example. [Diagram 2] 1 is an SEM image of granules contained in Powder 2 of the embodiment. [Diagram 3] 1 shows the pore size distribution of the powders of the examples and the powders of the comparative examples. [Figure 4]1 is a graph showing the time course of the adsorption amount of methylene blue to the powder of the examples. [Diagram 5] 1 is an X-ray diffraction chart of a powder of an example. [Figure 6] 1 is an X-ray diffraction chart of a powder of an example. [Figure 7] 1 shows the results of pore size distribution analysis by the BJH method for the powders of the examples. [Figure 8] 1 shows the results of pore size distribution analysis by the BJH method for the powders of the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, a numerical range expressed using "~" means a range that includes the numerical values before and after "~" as the lower and upper limits.
[0010] [Powder] The powder of the present invention is a powder containing aluminosilicate granules, and the aluminosilicate granules contain nanotube particles and magnetic particles. Since the aluminosilicate granules containing magnetic particles are subjected to a force corresponding to the magnetic field when placed in the magnetic field, the granules dispersed in the liquid can be easily collected. That is, for example, the aluminosilicate granules dispersed in the liquid are attracted to a magnet, facilitating solid-liquid separation. Furthermore, even when the aluminosilicate granules containing magnetic particles are mixed with other powders to form a mixed powder, they are attracted to a magnet, and therefore can be easily recovered or separated.
[0011] The content of the aluminosilicate granules is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, based on the total mass of the powder of the present invention. The upper limit of the content of the aluminosilicate granules in the powder of the present invention is not particularly limited, and may be 100% by mass based on the total mass of the powder. That is, the powder of the present invention may be composed of aluminosilicate granules.
[0012] In the aluminosilicate granules contained in the powder of the present invention, the molar ratio of the SiO2 content to the Al2O3 content (hereinafter simply referred to as "SiO2 / Al2O3") is not particularly limited, but is preferably 1.8 or more. In addition, SiO2 / Al2O3 is also preferably 2.1 or more, may be 3.0 or more, or may be 5.0 or more. The upper limit of SiO2 / Al2O3 is not particularly limited, and examples include 10,000 or less and 1,000 or less, preferably 500 or less, more preferably 300 or less, and even more preferably 200 or less. SiO2 / Al2O3 is determined by X-ray fluorescence (XRF) analysis. Specifically, XRF analysis is performed under the following conditions to determine SiO2 / Al2O3. Equipment used: ZSX Primus IV (Rigaku) ·Pretreatment method: Glass bead method using Li2B4O7 flux Quantitative method: Refractory Technology Association's standard sample for X-ray fluorescence analysis (clay brick standard sample series) and calibration curve method using other reagents
[0013] The aluminosilicate granules contained in the powder of the present invention include nanotube particles and magnetic particles. The aluminosilicate granules are not particularly limited as long as they include nanotube particles and magnetic particles, and may include other particles. Note that the nanotube particles and magnetic particles are preferably included as primary particles in the aluminosilicate granules. The aluminosilicate granules contained in the powder of the present invention each contain a nanotube-shaped particle and a magnetic particle, i.e., the aluminosilicate granules contained in the powder of the present invention are composite granules containing a nanotube-shaped particle and a magnetic particle. In the aluminosilicate granules, the magnetic particles may be distributed uniformly or unevenly. When the magnetic particles are unevenly distributed in the aluminosilicate granules, the magnetic particles may be unevenly distributed in the center part of the aluminosilicate granules, or may be unevenly distributed in the surface part of the aluminosilicate granules. In other words, when the magnetic particles are unevenly distributed in the aluminosilicate granules, the magnetic particles may be unevenly distributed as the core part, or may be unevenly distributed as the shell part. Here, the uneven distribution of the magnetic particles may be appropriately adjusted depending on the application of the powder, and for example, from the viewpoint of preventing deterioration of the magnetic particles or the liquid due to contact with the liquid, it is preferable that the magnetic particles are unevenly distributed in the core part.
[0014] The content of the nanotube particles in the aluminosilicate granules is preferably 70 mass % or more, more preferably 80 mass % or more, and even more preferably 85 mass % or more, based on the total mass of the aluminosilicate granules. The content of the magnetic particles in the aluminosilicate granules is preferably 2% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and particularly preferably 8% by mass or more, based on the total mass of the aluminosilicate granules, in order to facilitate separation and recovery operations. The content of the magnetic particles in the aluminosilicate granules is preferably 50% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less, and particularly preferably 15% by mass or less, in order to increase the amount of adsorption in the aluminosilicate granules, for example.
[0015] In this specification, the content of magnetic particles in the aluminosilicate granules is determined by a measurement method similar to the measurement method for SiO2 / Al2O3.
[0016] The nanotube particles and magnetic particles contained in the aluminosilicate granules will be described below.
[0017] <Nanotube particles> The nanotube particles are not particularly limited, but are preferably nanotube particles containing an alumina component and a silica component, and more preferably nanotube aluminosilicate particles. The nanotube particles preferably contain particles derived from halloysite nanotubes, which will be described later. The aluminosilicate granules may contain two or more kinds of nanotube particles.
[0018] Halloysite is a clay mineral expressed as Al2Si2O5(OH)4·2H2O or Al2Si2O5(OH)4. That is, the SiO2 / Al2O3 ratio in halloysite is generally 2.0. Halloysite generally exhibits a variety of shapes, such as tubular (hollow tubular), spherical, angular nodules, plates, and sheets. The inner diameter (diameter of the tube hole) of the halloysite nanotube particle, which is a tubular (hollow tubular) halloysite, is, for example, about 10 to 20 nm. The outer surface of the halloysite nanotube particle is mainly made of silicate (SiO2), and the inner surface is mainly made of alumina (Al2O3).
[0019] In addition, particles derived from halloysite nanotubes are a concept that includes halloysite nanotube particles and particles obtained by subjecting halloysite nanotube particles to the treatment described below (hereinafter also referred to as "modified halloysite nanotube particles"). Examples of modified halloysite nanotube particles include metahalloysite nanotube particles obtained by calcining halloysite, and acid-treated metahalloysite nanotube particles obtained by subjecting metahalloysite nanotube particles to an acid treatment. The aluminosilicate granules may contain only halloysite nanotube particles, may contain only modified halloysite nanotube particles, may contain halloysite nanotube particles and modified halloysite nanotube particles, or may contain two or more types of modified halloysite nanotube particles.
[0020] The metahalloysite nanotube particles that may be contained in the above-mentioned aluminosilicate granules refer to nanotube-shaped halloysite in which the OH of halloysite represented by Al2Si2O5(OH)4 has been dehydrated to give a low crystallinity, and metahalloysite has traditionally been used commonly or conventionally as a term representing a variant of halloysite. The metahalloysite nanotube particles are obtained by firing the halloysite nanotube particles at a predetermined temperature. The predetermined temperature is preferably 500° C. or higher, more preferably 600° C. or higher. The upper limit of the predetermined temperature is preferably 925° C. or lower, more preferably 900° C. or lower.
[0021] The acid-treated metahalloysite nanotube particles that can be contained in the above-mentioned aluminosilicate granules are obtained by subjecting metahalloysite nanotube particles to an acid treatment. The acid treatment refers to a treatment in which an acid treatment liquid is brought into contact with metahalloysite nanotube particles. The Al2O3 component in the metahalloysite nanotube particles is leached by the acid treatment. Acid-treated metahalloysite nanotube particles often have third pores with a pore size of 8 nm or less, and have unique adsorption properties derived from these pores. The acid-treated metahalloysite nanotube particles may be those which have been subjected to a calcination treatment after the acid treatment. The acid-treated metahalloysite nanotube particles may be obtained by subjecting aluminosilicate granules to acid treatment. After obtaining the acid-treated metahalloysite nanotube particles, a powder containing magnetic particles and acid-treated metahalloysite nanotube particles, which will be described in detail later, may be obtained.
[0022] <Magnetic particles> The magnetic particles are not particularly limited as long as they can be separated or recovered, but ferromagnetic particles are preferred. The ferromagnetic particles are preferably soft magnetic particles. Examples of the magnetic particles (preferably soft magnetic particles) include metal magnetic particles and oxide magnetic particles, and oxide magnetic particles are preferred.
[0023] Examples of materials constituting the metallic magnetic particles include metallic materials containing any one of the elements manganese, iron, cobalt, and nickel. An example of a material constituting the oxide magnetic particles is ferrite, which is made mainly of iron oxide, that is, an example of the oxide magnetic particles is ferrite particles.
[0024] The ferrite particles are not particularly limited, and ferrite particles having a known crystal structure and composition can be applied. For example, the crystal structure of the ferrite particles may be any of spinel type, magnetoplumbite type, and garnet type. Examples of components other than iron oxide contained in the spinel type ferrite particles include one or more elements selected from the group consisting of manganese, cobalt, nickel, copper, and zinc. Examples of components other than iron oxide contained in the magnetoplumbite type ferrite particles include one or more elements selected from the group consisting of barium, strontium, and lead. Examples of components other than iron oxide contained in the garnet type ferrite particles include one or more elements selected from the group consisting of rare earth elements.
[0025] As mentioned above, the magnetic particles are preferably soft magnetic particles. Examples of the soft magnetic particles include soft magnetic particles of simple metals such as iron, cobalt, and nickel, and soft magnetic particles of alloys containing these elements (Permalloy, Sendust (registered trademark)). The soft magnetic particles may be amorphous. Examples of the soft magnetic particles preferably include soft ferrites (e.g., MnZn ferrite, CuZn ferrite, and NiZn ferrite).
[0026] The type of magnetic particles can be appropriately selected depending on the application environment of the powder of the present invention. For example, when the powder of the present invention is used as an adsorbent as described below and a heat treatment is performed as a regeneration treatment, the magnetic particles preferably have heat resistance such that their physical properties do not change even when the heat treatment is performed. More specifically, when the heat treatment is performed in an oxygen-containing atmosphere, the magnetic particles are preferably oxide magnetic particles, and when the heat treatment is performed in a non-oxidizing atmosphere, the magnetic particles are preferably magnetic particles of a metal or alloy. In addition, it is preferable that the magnetic particles have a property that they are not altered by the liquid to which the powder of the present invention is applied.
[0027] The shape of the magnetic particles is not particularly limited, and may be any of spherical, flat, rod-like, polygonal columnar, and the like. The particle size of the magnetic particles is not particularly limited, but is preferably 10 nm to 10 μm, and more preferably 50 to 1000 nm.
[0028] Preferred properties of the powder of the present invention will now be described.
[0029] <Pore> The aluminosilicate granules contained in the powder of the present invention preferably have pores. The pores are preferably, for example, pores with a pore diameter of more than 8 nm and not more than 200 nm, more preferably pores with a pore diameter of more than 8 nm and not more than 100 nm. The presence or absence of pores can be confirmed by measuring an adsorption isotherm. Specifically, a nitrogen adsorption isotherm is obtained, and the nitrogen adsorption isotherm is analyzed by the BJH (Barrett-Joyner-Halenda) method, and a plot (Log differential pore volume distribution) is created with pore diameter on the horizontal axis and differential pore volume on the vertical axis, thereby confirming the presence or absence of pores in the above pore diameter range. The measurement conditions for obtaining the nitrogen adsorption isotherm will be described in detail in the Examples section below. The same applies to the other measurement conditions below.
[0030] The aluminosilicate granules contained in the powder of the present invention preferably have first pores derived from the tube pores of the nanotube particles and second pores different from the first pores. The second pores preferably correspond to the interparticle voids of the nanotube particles contained in the aluminosilicate granules. The pore diameters of the first pore and the second pore are preferably both in the range of more than 8 nm and not more than 200 nm, more preferably both in the range of more than 8 nm and not more than 100 nm, and even more preferably both in the range of 10 to 50 nm. The first pore is preferably in the range of 10 to 20 nm. It is also preferable that the Log differential pore volume distribution analyzed by the BJH method shows two or more pore diameter peaks in the above range. The presence or absence of pores having a pore size of more than 8 nm and not more than 200 nm (more preferably more than 8 nm and not more than 100 nm) and the presence or absence of the first pores and the second pores can also be confirmed by observing the aluminosilicate granules with an SEM. When the surface of the aluminosilicate granule is observed by SEM, the presence of the first pores derived from the tube structure of the nanotube particles can be confirmed, and when the cross section of the aluminosilicate granule is observed by SEM, the presence of the second pores can be confirmed. For example, the cross section of the aluminosilicate granule can be observed by cutting the aluminosilicate granule with a focused ion beam (FIB) to obtain a sample and then observing the sample.
[0031] Pores with diameters of more than 8 nm and not more than 200 nm are in the region including mesopores, and are thought to have excellent mass transport and adsorption properties, contributing to rapid reaction and adsorption.
[0032] The aluminosilicate granules contained in the powder of the present invention may have third pores with a pore size of 8 nm or less. The third pores with a pore size of 8 nm or less may be present together with the pores with a pore size of more than 8 nm and less than 200 nm. The aluminosilicate granules contained in the powder of the present invention may have the first pores with a pore size of more than 8 nm and less than 200 nm, the second pores with a pore size of more than 8 nm and less than 200 nm, and the third pores with a pore size of 8 nm or less. The presence or absence of third pores with a pore size of 8 nm or less can be confirmed by performing a so-called t-plot analysis of the nitrogen adsorption isotherm to confirm the presence or absence of micropores less than 2 nm, or by fitting the nitrogen adsorption isotherm using the Grand canonical Monte Carlo (GCMC) method to obtain a pore size distribution. The third pores having a pore size of 8 nm or less are, for example, possessed by acid-treated metahalloysite nanotube particles, so that, for example, when an aluminosilicate granule contains an acid-treated metahalloysite nanotube particle, the aluminosilicate granule has a third pore having a pore size of 8 nm or less. Note that general halloysite nanotube particles do not have a third pore having a pore size of 8 nm or less. The pore diameter of the third pores having a pore diameter of 8 nm or less is preferably, for example, 1 to 5 nm. The third pores having a pore diameter of 8 nm or less may have multiple peaks in the range of 8 nm or less in the pore diameter distribution obtained by the above method.
[0033] The third pores, with a pore size of 8 nm or less, are nanospaces in a region close to the size of molecules, and therefore can function as specific reaction sites and specific adsorption sites for molecules.
[0034] The aluminosilicate granules contained in the powder of the present invention may have pores having a pore size of more than 200 nm. The pores having a pore size of more than 200 nm may be present together with at least one of the pores having a pore size of more than 8 nm and not more than 200 nm, and the third pores having a pore size of not more than 8 nm. The presence or absence of pores with a pore diameter of more than 200 nm can be confirmed by observing the surface of the aluminosilicate granules with an SEM. In this specification, the size of pores with a pore diameter of more than 200 nm refers to the diameter of the pores observed from the surface of the aluminosilicate granules when the surface is observed with an SEM. When the shape of the pores is not a perfect circle, the distance between two parallel lines that are tangent to the shape of the pores is the longest, and the pore diameter of the pores with a pore diameter of more than 200 nm is the longest. The pore diameter of the pores with a pore diameter of more than 200 nm is preferably 5000 nm or less.
[0035] Pores with a diameter of more than 200 nm are believed to contribute to the promotion of adsorption and reaction of solid substances because they enable the adsorption of larger objects. For example, when the pores have a diameter of more than 100 nm, it is possible to capture dust, viruses, bacteria, pollen, etc. and react with them (for example, inactivate them).
[0036] <Specific surface area> The specific surface area (BET specific surface area) of the powder of the present invention is 30 m 2 / g or more is preferable, and 50m 2 / g or more is more preferable. Also, the BET specific surface area is 80m 2 The upper limit of the BET specific surface area is not particularly limited, but may be, for example, 1000 m 2 / g or less, and 600m 2 / g or less. The BET specific surface area is usually 200m 2 / g or less. The BET specific surface area can be determined by applying the BET method to a nitrogen adsorption isotherm.
[0037] <Pore volume> The total pore volume of the powder of the present invention is 0.20 cm 3 / g or more is preferable, and 0.23 cm 3 / g or more is more preferable. The total pore volume is 0.45 cm 3 The upper limit of the total pore volume is not particularly limited, but may be, for example, 2.00 cm 3 / g or less, and 1.20 cm 3 / g or less. The total pore volume is usually 0.80 cm 3 / g or less. The total pore volume is calculated from the adsorption amount at a relative pressure of 0.99 from the nitrogen adsorption isotherm using the following formula. Vp = V / 22414 × Mg / ρg Vp: total pore volume up to relative pressure (0.99) V: Adsorption amount at relative pressure (0.99) 22414:Volume of gas per mole Mg: Molecular weight of adsorbate (N2) (28.013) ρg: Density of the adsorbate (N2) (0.808)
[0038] In addition, when the powder of the present invention has micropores (2 nm or less), the volume of the micropores is 0.01 cm 3 / g or more is preferable, and 0.02 cm 3 / g or more is more preferable, and 0.04 cm 3 / g or more is more preferable, and 0.08 cm 3 The upper limit of the volume of the micropores is not particularly limited, but is, for example, 0.5 cm 3 / g or less, and 0.2 cm 3 / g or less in most cases.
[0039] <Other components and other particles> In the powder of the present invention, the aluminosilicate granules may contain components other than the nanotube particles and the magnetic particles. For example, the aluminosilicate granules may contain a catalytic component that drives a desired reaction. The catalytic component may be supported on the aluminosilicate granules or nanotubular particles as particles, or as clusters of single atoms or a few atoms. The catalytic component may also be supported on the aluminosilicate granules and nanotubular particles. The elements contained in the catalyst component are not particularly limited and can be selected according to the desired reaction. Examples of elements contained in the catalyst component include Group 1 elements to Group 17 elements, and often contain transition metal elements or rare earth elements. The type of element contained in the catalyst component may be one type, or two or more types. The above-mentioned catalyst component is a concept that includes not only a catalyst component that advances a desired reaction, but also a so-called co-catalyst that promotes the progress of the desired reaction. The catalyst component may be a known one, and the catalyst component may be supported by a known method.
[0040] In the powder of the present invention, the aluminosilicate granules may contain a pharmaceutical component as a component other than the nanotube particles and magnetic particles. The medicinal component is not particularly limited, and examples thereof include known deodorant components, antibacterial components, germicidal components, and pharmaceutical components.
[0041] Furthermore, the aluminosilicate granules in the powder of the present invention may contain particles (other particles) other than the nanotube particles. The other particles are not particularly limited, but examples thereof include colorant particles, drug particles containing a drug component, and particles containing each of the above components.
[0042] <Powder characteristics> The average particle size of the powder of the present invention is not particularly limited and may be appropriately selected depending on the application, but is, for example, 0.5 to 200 μm, preferably 1 to 100 μm. The powder of the present invention may be granulated before use. The size of the granulated powder is preferably 5 mm or less. The average particle size is measured using a laser diffraction / scattering particle size distribution analyzer (Microtrac MT3300EXII) manufactured by Microtrac Bell.
[0043] The powder of the present invention is also preferably such that the breaking strength of the aluminosilicate granules is 5.0 MPa or more. When the aluminosilicate granules contained in the powder of the present invention have the above breaking strength, the pores (e.g., the first pores and the second pores, particularly the second pores) having a pore size of more than 8 nm and not more than 200 nm are easily maintained. Therefore, when the aluminosilicate granules contained in the powder of the present invention have the above breaking strength, they are not easily broken during handling, pretreatment (e.g., dispersion treatment), and composite treatment (e.g., kneading with resin), and the like, and the pores can be maintained. On the other hand, so-called silica gel, mesoporous silica, activated carbon, and other general porous materials often have low particle breaking strength, and the particles may be broken during the above operations, making it impossible to maintain the pore structure. The breaking strength is more preferably 6.0 MPa or more, and even more preferably 7.0 MPa or more. The upper limit of the breaking strength is not particularly limited, and is, for example, 60.0 MPa or less, preferably 50.0 MPa or less, and more preferably 45.0 MPa or less.
[0044] The breaking strength of the aluminosilicate granules is measured by a compression test using a micro compression tester, and is the average value of five test results. More specifically, the aluminosilicate granules contained in the powder of the present invention are first used as a sample. A very small amount of this sample is scattered on the sample stage (lower pressure plate) of a micro compression tester MCT-510 (manufactured by Shimadzu Corporation), and a compression test is performed on each sample grain to determine the breaking strength. Usually, the average value of five test results (breaking strength) is taken as the breaking strength of the powder. The breaking strength is calculated by measuring the diameters of each sample particle in the X and Y directions on the sample stage, taking the average value as the particle size of each sample particle, and using the following formula (1). (1) Cs = 2.48 × P / (πd 2 ) In formula (1), Cs is the breaking strength (unit: MPa), P is the breaking test force (unit: N), and d is the diameter of the sample particle (unit: mm).
[0045] In addition, it is also preferable that the powder of the present invention has a hydrous breaking strength of 80% or more of the above breaking strength when the aluminosilicate granules are immersed in pure water for 24 hours to be hydrous. The hydrous breaking strength may be the same value as the above breaking strength, i.e., 100%. When the hydrous breaking strength is excellent, the pore structure is easily maintained even in applications where the powder comes into contact with aqueous solutions, etc., which is preferable. The wet fracture strength is measured in the same manner as in the above-mentioned method for measuring fracture strength, except that the sample is aluminosilicate granules that have been immersed in pure water for 24 hours to become wet.
[0046] The methylene blue adsorption amount of the powder of the present invention is preferably 10 mg / g or more, more preferably 15 mg / g or more, and even more preferably 20 mg / g or more. The methylene blue adsorption amount may be 40 mg / g or more. There is no particular upper limit to the methylene blue adsorption amount, but it may be, for example, 200 mg / g or less, and is often 100 mg / g or less. The methylene blue adsorption amount may be 50 mg / g or less. The above methylene blue adsorption amount indicates the amount of methylene blue adsorbed per gram of the powder of the present invention. The amount of methylene blue adsorbed per gram of powder is calculated from the concentration of the methylene blue solution before it comes into contact with the powder (pre-contact concentration), the concentration of the methylene blue solution obtained after stirring the powder and methylene blue solution overnight and then separating the solid-liquid phase using a centrifuge (post-contact concentration), the amount of methylene blue solution used, and the amount of powder added. The concentration of methylene blue is measured from the absorbance at 664.5 nm.
[0047] [Powder applications] The powder of the present invention can be used in various applications that utilize the pores derived from the nanotube particles. The powder of the present invention can be preferably used, for example, as an adsorbent. Furthermore, the powder of the present invention is not limited to use as an adsorbent, but can be applied to a wide variety of applications. Examples of uses include deodorizing materials, water purification materials, artificial enzymes, catalysts, catalyst carriers, sustained-release materials, antibacterial materials, disinfectants, precision polishing materials, magnetorheological fluids, cosmetics, coloring materials, food, fermentation, and pharmaceuticals, but it goes without saying that the uses are not limited to these.
[0048] Furthermore, since the powder of the present invention is subjected to a force corresponding to the magnetic field when placed in the magnetic field (is attracted to a magnet), it can also be used in applications that utilize this function. For example, since the powder of the present invention can be easily separated into solid and liquid, it is particularly suitable for use in applications in which the powder is dispersed in a liquid for processing and then recovered after processing. The powder of the present invention can also be preferably used in applications in which it is mixed with other powders, the resulting mixed powder is used for processing, and the powder is then recovered after processing. In addition, for example, components in a liquid or gas phase can be easily adsorbed into the powder and the powder to which the components have been adsorbed can be easily removed or transported, making the powder suitable for use in applications in which adsorption removal or recovery operations are performed.
[0049] As described above, the powder of the present invention has pores and is also capable of being attracted to a magnet, and therefore can be used in a variety of applications.
[0050] Furthermore, when the powder of the present invention is used as a heterogeneous catalyst, a solid acid catalyst, or a support for a catalyst component, the reactants are easily diffused, and high activity can be expected. When the powder of the present invention has the above-mentioned pores (for example, one or more of the first pore, the second pore, and the third pore), particularly high activity can be expected. Here, by utilizing the property of the powder of the present invention that it is subjected to a force corresponding to a magnetic field, when the reaction phase of a catalytic reaction is a liquid phase, it is possible to recover the catalyst (the powder of the present invention) from the liquid phase without performing filtration separation, which is considered to have the advantage of being applicable to industrial processes, etc. Furthermore, even when the powder of the present invention is used in combination with other powders in a packed bed in a catalytic reaction in a flow method in the liquid or gas phase, it can be said that the powder of the present invention can be easily recovered after the reaction, etc.
[0051] The powder of the present invention is also expected to be used as a drug delivery system (DDS). Specifically, the pore structure is expected to have the function of controlling the release of drugs, and the targeting function can be controlled by magnetism. The powder of the present invention is also suggested to be applicable to processing, etc. Specifically, if the aluminosilicate granules are soaked in a drug and then moved to a predetermined position by a magnetic field, and the drug is then released, the drug can be selectively released at a predetermined position, and it is expected that the drug can be processed into a desired pattern shape.
[0052] When the powder of the present invention is used as an adsorbent, the powder of the present invention that has adsorbed an adsorbent may be regenerated and used again as an adsorbent. The regeneration treatment is not particularly limited as long as the adsorbed substances are removed from the powder, and can be appropriately selected depending on the type of the adsorbed substances. Examples of the regeneration treatment include a heat treatment in which the powder is heated, and an extraction treatment in which the powder is brought into contact with a liquid in which the adsorbed substances are easily dissolved. The powder of the present invention is unlikely to lose its adsorption ability even when subjected to heat treatment, and can be regenerated by heating at a high temperature, preferably at 300°C or higher, but may also be 500°C or higher, 600°C or higher, 800°C or higher, or 900°C or higher.
[0053] Furthermore, the above-mentioned regeneration treatment can be preferably applied when the powder of the present invention is used as a catalyst or the like. In the regeneration process, the powder of the present invention is easy to separate and recover.
[0054] [Powder manufacturing method] The method for producing the powder of the present invention (hereinafter, for convenience, also referred to as the "production method of the present invention") will be described. The manufacturing method of the present invention preferably includes at least a step of preparing a slurry containing nanotube particles and magnetic particles (slurry preparation step), and a step of preparing a powder from the slurry (powder preparation step), thereby obtaining aluminosilicate granules in which the nanotube particles and the magnetic particles are aggregated. Hereinafter, a preferred embodiment of the production method of the present invention in which the nanotube particles include halloysite nanotube particles will be described.
[0055] <Slurry preparation process> (Raw material (Halloysite)) As the raw material halloysite used in the manufacturing method of the present invention (hereinafter also referred to as "raw material halloysite"), commercially available halloysite (halloysite nanotubes) can be used, and specifically, for example, halloysite manufactured by APPLIED MINERALS (product name: DRAGONITE-HP) can be suitably mentioned.
[0056] (Slurrying) First, a slurry in which the raw halloysite is dispersed in water is obtained. The method for dispersing the raw halloysite in water is not particularly limited, and for example, a conventionally known device such as a high-speed mixer, a disperser, a bead mill, or a homomixer can be used. The solid content concentration of the slurry is not particularly limited and is, for example, 30 to 50 mass %.
[0057] It is preferable to add a dispersant to the slurry because it is closely related to the accuracy of the centrifugation described later. By adding a dispersant, a slurry with a higher concentration can be obtained, which also has the effect of improving the productivity in drying using a spray dryer or the like described later.
[0058] The dispersant is preferably one that can provide a stable slurry with a small amount of use, and examples thereof include polymer-type anionic surfactants (anionic polymer surfactants). Specific examples of anionic polymer surfactants include special polycarboxylic acid type Poise 520, 521, and 530 (all manufactured by Kao Corporation). Depending on the intended use, Poise 532A, Caocera 2000, 2020 and 2110 (ibid.), which do not contain metal ions such as sodium and potassium, can also be used. Furthermore, the anionic polymer surfactant is not limited to the polycarboxylic acid type, and acrylic acid type, sulfonic acid type, etc. can also be used.
[0059] The content of the dispersant is not particularly limited, but a suitable example is 0.5 to 3.0 mass % based on the total solid content in the slurry. If the dispersant content is too low, the halloysite and impurity particles may not be sufficiently dispersed in the slurry. On the other hand, if the dispersant content is too high, it may cause agglomeration or increase costs. Furthermore, it may be prone to problems in downstream processes (such as a decrease in the recovery rate of the dispersed phase during centrifugation, insufficient drying during spray drying, or insufficient caking or burning during firing).
[0060] (coarse grain removal) In order to increase the accuracy of the centrifugation described later, coarse particles in the slurry may be removed. For example, a sieve with 25 to 100 μm openings or a wet cyclone may be used to remove the coarse particles. Alternatively, the slurry may be allowed to settle and separate to remove the coarse particles.
[0061] (Centrifugation) The obtained slurry is centrifuged to separate it into a lower sedimentation phase and an upper dispersed phase. The sedimentation phase contains many impurities such as fine sand, and the dispersed phase contains many halloysite nanotube particles. The solid content of the dispersed phase (slurry) is, for example, 10 to 30% by mass. The centrifugal force and processing time during centrifugation are, for example, 2000 to 3000 G and 3 to 30 minutes, respectively, but are not limited to these values and are appropriately set in consideration of the dispersion state, application, cost, and the like. Larger centrifuges can also be used for mass production. By recovering the dispersed phase, the halloysite nanotube particles can be purified and separated from the raw halloysite containing impurities such as fine sand.
[0062] (Addition of magnetic particles) The magnetic particles are added to the collected dispersed phase (slurry). The amount of magnetic particles added is, for example, such that the content of the magnetic particles in the slurry after the addition is 2 to 50 mass % relative to the total amount of the halloysite nanotube particles and the magnetic particles in the slurry, but is not limited thereto. After the addition, the magnetic particles are dispersed in the slurry. The method for dispersing the magnetic particles in the slurry is not particularly limited, and for example, a conventionally known device such as a high-speed mixer, a disperser, a bead mill, or a homomixer can be used. The slurry obtained in the slurry preparation step may be subjected to operations such as purification, classification, magnetic separation, and concentration, if necessary. The magnetic particles may be prepared as described above in the preferred embodiment. Commercially available magnetic particles may also be used.
[0063] <Powder preparation process> The powder preparation step is a step of preparing powder from the slurry prepared in the slurry preparation step. The powder obtained in the powder preparation step may be further granulated by subjecting it to treatments such as rolling, stirring, extrusion, etc. This allows the size of the granules constituting the powder to be increased.
[0064] (Spray drying) An example of the powder preparation step is a step of obtaining a powder by spray drying the slurry prepared in the slurry preparation step.
[0065] To spray-dry the prepared slurry, a spray dryer is used, which is a device that sprays (atomises) the liquid raw material into fine droplets and dries them with hot air to instantly obtain powder. Spray dryers are conventionally known devices, and examples of such spray dryers include those manufactured by Okawara Kakoki Co., Ltd., Fujisaki Electric Co., Ltd., and Nippon Kagaku Kikai Seizo Co., Ltd. In a spray dryer, the particle size of the powder particles (granules) obtained by drying can be controlled by changing the size of the droplets obtained by spraying (atomizing) the liquid raw material. The method of atomizing the liquid raw material using a spray dryer is not particularly limited, and a conventionally known method such as a two-fluid nozzle method, a pressure nozzle (pressurized nozzle) method, a four-fluid nozzle method (twin jet nozzle method), or a rotating disk method can be appropriately selected depending on the desired droplet size. Since the particle size of the powder particles (granules) obtained by drying varies depending on the concentration of the slurry and / or the processing amount, in order to obtain the desired particle size, in addition to the atomization method, the state of the slurry must be appropriately selected. The contact method between the hot air and the sprayed droplets can be appropriately selected from the following types: a general parallel flow type in which the hot air and sprayed droplets both flow downward; a counter flow type in which the hot air flows upward in a counterflow direction while the sprayed droplets flow downward; and a parallel counter flow type in which the sprayed droplets flow upward and the hot air flows downward.
[0066] Spray drying applies heat instantaneously, so the powder itself does not easily become hot. Spray drying dries the slurry to obtain powder directly, so there is no need for processes such as filtration, drying, and pulverization, and contamination that may occur during these steps can be suppressed.
[0067] The method for obtaining powder by the spray drying process has been described above. On the other hand, as mentioned above, the method for obtaining powder is not particularly limited, and may be, for example, a method for drying the above-mentioned slurry in a fluidized bed (ball-containing fluidized bed drying). In the medium fluidized drying, the slurry to be dried is first continuously fed to a layer of ceramic balls of 1 to 3 mm diameter in a fluidized state, so that the slurry adheres to the ball surfaces. The material to be dried is instantly dried by heat conduction from the heated balls and convection heat transfer from the fluidized hot air, and is peeled off from the ball surfaces by collision between the balls. In this way, powder (aluminosilicate granules) is obtained.
[0068] By adjusting the procedure and conditions for obtaining the powder, the particle size of the granules in the obtained powder can be adjusted.
[0069] <Firing process> The method for producing halloysite powder of the present invention may further include a step of calcining the powder obtained in the powder preparation step (calcination step).
[0070] When a surfactant is used in the above-mentioned post-slurrying, the surfactant may remain in the powder obtained by spray drying or the like, but by carrying out firing in an air atmosphere, the surfactant can be effectively removed. Furthermore, by carrying out the firing step, the above-mentioned breaking strength of the aluminosilicate granules contained in the powder can be improved.
[0071] The firing temperature is preferably a temperature at which the tubular structure of halloysite or metahalloysite can be maintained. Specifically, the firing temperature is preferably 200°C or higher, more preferably 300°C or higher, and even more preferably 400°C or higher. On the other hand, the firing temperature is preferably 1000°C or lower, more preferably 900°C or lower, and even more preferably 800°C or lower. The firing time is preferably 0.5 hours or more, more preferably 0.75 hours or more, while the firing time is preferably 10 hours or less, more preferably 5 hours or less.
[0072] The firing atmosphere is not particularly limited, and may be, for example, an air atmosphere.
[0073] When the production method of the present invention does not include a firing step, the powder obtained in the powder preparation step is the powder of the present invention. On the other hand, when the production method of the present invention includes a firing step, the powder fired in the firing step becomes the powder of the present invention.
[0074] In the manufacturing method of the present invention, it is also preferable to mix particles of a material (template particles) that disappear in the firing step as primary particles in the slurry to be subjected to the spray drying step. When the slurry containing the template particles is subjected to the spray drying step, aluminosilicate granules containing template particles, nanotube particles, and magnetic particles are obtained. When the powder containing such aluminosilicate granules is subjected to the firing step and the acid treatment step, the template particles are removed and pores corresponding to the shape of the template particles are generated. By adjusting the shape and amount of the template particles, the spray drying conditions, etc., it is possible to generate macropores of a desired shape. The template particles of the material that disappears during the firing step are not particularly limited, but examples thereof include resin particles and carbon particles.
[0075] In the above, the method of spray-drying a slurry containing halloysite nanotube particles and magnetic particles has been described as the production method of the present invention, but the powder of the present invention may be produced by methods other than the above. As a manufacturing method other than the above, for example, the solvent component may be removed by drying from a slurry containing nanotube particles and magnetic particles to obtain a molded body, and the molded body may be crushed to an appropriate size to obtain the powder of the present invention. In addition, in the manufacturing method of the present invention, at least one of metahalloysite nanotube particles obtained by a calcination treatment and acid-treated metahalloysite nanotube particles obtained by a calcination treatment and an acid treatment may be used as the halloysite nanotube particles. In the manufacturing method of the present invention, the powder of the present invention obtained through the above-mentioned calcination step may be further treated with an acid to obtain the powder of the present invention. The powder obtained by the acid treatment may be further washed. The powder obtained by the acid treatment or the powder obtained by washing may be further subjected to a calcination step to obtain the powder of the present invention. The powder obtained by the acid treatment of the powder of the present invention obtained through the calcination step often has third pores with a pore size of 8 nm or less, which is preferable. EXAMPLES
[0076] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the following examples.
[0077] [Example 1] Powder 1, which corresponds to the powder of the present invention, was produced by the following procedure.
[0078] <Raw material halloysite> As the raw material halloysite, halloysite manufactured by APPLIED MINERALS (product name: DRAGONITE-HP) was prepared.
[0079] <Slurrying> Raw halloysite, water and anionic polymer surfactant (Kao Corporation, Poise 530A) were placed in a high-speed mixer (Nihon Seiki Seisakusho, Ultra Homo Mixer UHM-20 (20 liters)) and processed at 10,000 rpm for 10 minutes to obtain a slurry (solid content concentration: 40% by mass) in which raw halloysite was dispersed in water. The content of the anionic polymer surfactant relative to the total solid content of the slurry was 2.0% by mass.
[0080] <Centrifugation> The slurry was centrifuged for 10 minutes at a centrifugal force of 2500G using a centrifuge (Kubota Shoji Co., Ltd., high-speed, large-capacity refrigerated centrifuge 7000), the slurry was separated into a precipitated phase and a dispersed phase, and the dispersed phase was collected. The solid content of the collected dispersed phase (slurry) was 24% by mass. The solid content was measured using a halogen heating moisture meter (Shinko Denshi Co., Ltd., MA-120) at a dry heat treatment temperature of 200°C.
[0081] <Addition of magnetic particles> The magnetic particles were added to the recovered dispersed phase (slurry), and the mixture was treated at 10,000 rpm for 10 minutes using a high-speed mixer (Ultra Homo Mixer UHM-20, manufactured by Nippon Seiki Seisakusho) to disperse the magnetic particles in the slurry. The added magnetic particles were NiCuZn ferrite particles (KNI-106, manufactured by JFE Chemical Corporation, hereinafter also referred to as "NiCuZn particles"). The average particle size of the NiCuZn particles was measured using a laser diffraction / scattering particle size distribution analyzer (Microtrac MT3300EXII) manufactured by Microtrac Bell Co., Ltd. As a result, the average particle size of the NiCuZn particles was 3.7 μm. The amount of magnetic particles added is as shown in Table 1 below.
[0082] <Spray drying> The slurry to which the magnetic particles were added was spray-dried using a spray dryer to obtain granules containing the magnetic particles. The spray dryer used was a spray dryer L-8i manufactured by Okawara Kakoki Co., Ltd., and the slurry was supplied in a fixed amount by a pump to atomize (spray) the slurry. The spray drying conditions are as follows: Atomization method: Four-fluid nozzle method Spray air pressure: 0.20MPa Water evaporation rate: 2.5kg / h ·Inlet temperature: 190℃ ·Outlet temperature: 80℃
[0083] <Firing process> The obtained granules were fired to obtain aluminosilicate granules containing magnetic particles and metahalloysite nanotube particles. Specifically, the obtained granules were sintered in an air atmosphere by introducing air into an electric furnace with a siliconite heating element. The sintering conditions were a temperature rise rate of 4°C / min, and after reaching 900°C, the temperature was maintained at 900°C for 1 hour, and then the furnace was cooled.
[0084] [Example 2] The powder of Example 2 (Powder 2) was obtained in the same manner as the powder of Example 1, except that in the procedure for obtaining the powder of Example 1 (Powder 1), the amount of magnetic particles added to the slurry was changed to the amount shown in Table 1 below.
[0085] [Example 3] The powder of Example 3 (Powder 3) was obtained in the same manner as the powder of Example 1, except that in the procedure for obtaining the powder of Example 1 (Powder 1), the magnetic particles added to the slurry were changed to MnZn ferrite particles (LD-M, manufactured by JFE Chemical Corporation; hereinafter, also referred to as "MnZn particles") and the amount of the magnetic particles added to the slurry was changed to the amount shown in Table 1 below. The average particle size of the MnZn particles was measured using a laser diffraction / scattering particle size distribution analyzer (Microtrac MT3300EXII) manufactured by Microtrac Bell Co., Ltd. As a result, the average particle size of the MnZn particles was 9.7 μm.
[0086] [Comparative Example 1] Powder 4 not containing magnetic particles was obtained in the same manner as in the procedure for obtaining Powder 1 described above, except that magnetic particles were not added to the slurry to be subjected to spray drying.
[0087] [Table 1]
[0088] [Powder evaluation] The powders 1 to 4 obtained by the above procedure were evaluated as follows.
[0089] <xrd> The X-ray diffraction charts of Powders 1 to 3 are shown in Fig. 1. The sharp diffraction peaks in each chart are peaks attributed to the crystal structures of NiCuZn particles or MnZn particles, and almost no diffraction peaks corresponding to halloysite nanotube particles were observed. This is presumably because the crystal water in the halloysite nanotube particles was desorbed by the above firing process, and the halloysite nanotube particles were amorphized and changed into metahalloysite nanotube particles.
[0090] <SEM Observation> Each powder was observed by SEM. The results of observing the granules contained in Powder 2 typically are presented. Fig. 2 is an SEM image of the granules of Powder 2. From the SEM image of Fig. 2, it was confirmed that Powder 2 contains granules (aluminosilicate granules) formed by the aggregation of halloysite containing halloysite nanotube particles. Further, it was confirmed that pores (first pores) derived from the tube pores of the halloysite nanotube particles and pores (second pores) having a larger diameter than the tube pores of the halloysite nanotube particles exist on the surface of the granules. Furthermore, in the SEM image of Fig. 2, since almost no magnetic particles were observed on the surface thereof, it can be inferred that the magnetic particles have a structure covered with halloysite nanotube particles. That is, it can be inferred that in the obtained aluminosilicate granules, many magnetic particles are present in the core part. Note that similar SEM observation images were also obtained for Powder 1 and Powder 3.
[0091] <Nitrogen Adsorption Isotherm> In the present invention, nitrogen adsorption isotherms were obtained under the following conditions and procedures, and various analyses were performed. First, after the powder was pretreated (vacuum degassing at 120°C for 8 hours), the adsorption isotherm and desorption isotherm of nitrogen were measured under the following conditions using the constant volume method. The equilibrium waiting time is the waiting time after reaching the adsorption equilibrium state. · Adsorption temperature: 77K Cross section of nitrogen: 0.162nm 2 Saturated vapor pressure: Actual measurement Equilibration wait time: 500sec Pretreatment device: BELPREP-vacII (Microtrack, BEL) Measurement device: BELSORP-mini (Microtrack BEL) Analysis software: BELMaster Version 6.4.0.0 (Microtrack-Bell)
[0092] BET specific surface area [m 2 / g] was determined by applying the BET method from the nitrogen adsorption isotherm as described above. The BET specific surface areas and total pore volumes of Powders 1 to 4 obtained by the above measurements and analyses are shown in Table 2 below. The total pore volume was calculated from the adsorption amount at a relative pressure of 0.99 from the nitrogen adsorption isotherm as described above.
[0093] Furthermore, the nitrogen adsorption isotherms of Powders 1 to 4 were analyzed for pore size distribution by the BJH method. The results are shown in Figure 3. In each graph, the horizontal axis represents pore size [nm], and the vertical axis represents differential pore volume (dVp / dlogDp) [cm 3 In the graph of FIG. 3, two or more pore size peaks were confirmed within the range of 10 nm or more (more than 8 nm and 100 nm or less). The peak observed near 20 nm corresponds to the first pores originating from the tube pores of the nanotube particles, and the peak observed near 50 nm corresponds to the second pores corresponding to the interparticle voids of the nanotube particles.
[0094] <Average particle size> The average particle sizes of Powders 1 to 4 were measured by the method described above, and the results are shown in Table 2 below.
[0095] [Table 2]
[0096] <Methylene blue adsorption test and solid-liquid separation test> First, a methylene blue solution for bacterial staining manufactured by Sigma-Aldrich (methylene blue concentration in 100 mL: 0.5% by mass) was diluted with pure water to prepare a methylene blue solution with a concentration of 0.02% by mass. The centrifuge tubes containing 50 mL of the prepared methylene blue solution and 0.75 g of each powder were placed in a tube rotator (MX-RL-Pro, manufactured by AS ONE Corporation) and stirred at room temperature for 24 hours. After stirring, the contents of the centrifuge tube were subjected to solid-liquid separation by applying a centrifugal force of 3000 G for 15 minutes using a centrifuge (Kubota Shoji Co., Ltd., high-speed, large-capacity refrigerated centrifuge 7000). When the solid-liquid separated contents were visually observed, the settled solid side was blue, while the liquid side was almost colorless and transparent. It was also confirmed that when only the methylene blue solution was subjected to centrifugal force under the same conditions as above, the methylene blue solution showed a uniform blue color. Therefore, it is believed that methylene blue molecules were adsorbed onto each powder. In this case, the amount of methylene blue adsorbed per gram of each powder was estimated to be 13 mg / g.
[0097] In addition, using the same procedure as above, the dispersion liquid in which Powder 1 with methylene blue adsorbed thereto was dispersed after stirring at room temperature for 24 hours was transferred to a glass petri dish and a commercially available neodymium magnet was placed on the bottom of the dish, whereupon the blue Powder 1 was attracted, allowing the liquid to be separated into a colorless, transparent liquid phase and Powder 1. That is, it was confirmed that Powder 1 (the powder of the present invention) can be easily separated into solid and liquid after being dispersed in a liquid and treated. More specifically, it was confirmed that Powder 1 can be easily separated into solid and liquid by a simple operation using magnetic force after being dispersed in a liquid and treated to adsorb the adsorbate, and Powder 1 with the adsorbate adsorbed thereto can be easily recovered. Like powder 1, powders 2 and 3 were also attracted to the magnet and separated into a colorless and transparent liquid phase and powder 2 or powder 3. On the other hand, Powder 4 was not attracted to the magnet and solid-liquid separation was not possible.
[0098] <Repeated adsorption characteristics> Powder 1 with methylene blue adsorbed was recovered by solid-liquid separation and calcined at 900°C for 1 hour, after which the blue color of Powder 1 disappeared. In other words, it is presumed that methylene blue was desorbed from Powder 1 by the calcination. In this way, the regeneration process by heating was performed, and methylene blue was adsorbed again onto the regenerated powder 1, and the amount of adsorption was estimated. Furthermore, the above-mentioned regeneration process was performed on the powder 1 to which methylene blue had been adsorbed again. The above-mentioned adsorption of methylene blue and the transition of the saturated adsorption amount of methylene blue on powder 1 were measured when the regeneration process was repeatedly performed. In the same manner, the transition of the saturated adsorption amount of methylene blue on powder 2 and powder 3 were also measured. The results are shown in Figure 4. The saturated adsorption amount was determined by the method described above. Specifically, each powder was added to a 0.02% by mass methylene blue solution in an amount of 1 / 200 of the amount of the methylene blue aqueous solution, and the methylene blue adsorption amount per gram of powder was calculated from the concentration of the methylene blue solution before and after contact with the powder.
[0099] From the results shown in FIG. 4, it was confirmed that Powder 1, Powder 2 and Powder 3 (powders of the present invention) maintained the adsorption amount of methylene blue even after repeated regeneration treatment by heating.
[0100] [Example 4] Powder 1 obtained in Example 1 above was subjected to an acid treatment in the following manner to obtain Powder 5. For the acid treatment, hydrochloric acid (acid treatment liquid) of the following concentration was used. The acid treatment was carried out by putting the above powder 1 and the below-mentioned acid treatment liquid into a glass beaker and stirring with a PTFE stirring blade. The acid treatment was carried out by heating the glass beaker with a mantle heater and controlling the liquid temperature to the following temperature. After the acid treatment, suction filtration was performed to separate the solid and liquid, and then a process of dispersing the product in ion-exchanged water and a process of performing solid-liquid separation (washing process) were repeatedly performed using ion-exchanged water until the conductivity of the filtrate reached the following value. After the washing step, drying was carried out at 110° C. to obtain a powder (Powder 5).
[0101] <Acid treatment conditions> Acid treatment solution: 2mol / L hydrochloric acid Liquid temperature: 60℃ Duration: 2 hours Ratio of mass of acid treatment solution to mass of calcined or uncalcined powder (powder / acid treatment solution): 25 Filtrate conductivity at the end of washing: 1mS / m
[0102] [Example 5] The powder of Example 5 (Powder 6) was obtained in the same manner as in Example 4, except that in the procedure for obtaining Powder 5 of Example 4, the powder subjected to the acid treatment was changed from the powder of Example 1 (Powder 1) to the powder of Example 3 (Powder 3).
[0103] [Example 6] Powder 5 obtained by the above procedure was further calcined (post-calcined) at 900° C. for 1 hour to obtain powder (powder 7).
[0104] [Example 7] Powder 5 obtained by the above procedure was further calcined (post-calcined) at 900° C. for 1 hour to obtain powder (powder 8).
[0105] [Powder evaluation] Powders 5 to 8 obtained by the above procedure were evaluated in the same manner as for powders 1 to 4. The results will be described.
[0106] First, Table 3 shows the saturated adsorption amount of methylene blue for powders before and after acid treatment. Note that the post-baking temperatures shown in the columns for Powder 5 and Powder 6 in Table 3 are the drying temperatures described above.
[0107] [Table 3]
[0108] The results shown in Table 3 show that Powders 5 to 8 obtained by acid treatment each had an increased amount of methylene blue adsorbed, compared with Powders 1 and 3 which were powders before the acid treatment. Furthermore, from the results shown in Table 3, when comparing the powders before the acid treatment (powders 1 and 3) with the powders after the acid treatment (powders 5 and 7, and powders 6 and 8), it can be seen that the BET specific surface area and total pore volume of the powders after the acid treatment are increased. Powders 5 to 8, which had adsorbed methylene blue and were dispersed in the dispersion liquid, were also attracted to the magnet in the same manner as powder 1 and the like. Furthermore, it was confirmed that Powders 5 to 8 were attracted to a neodymium magnet even in a dry state.
[0109] 5 and 6 show the X-ray diffraction charts of Powder 5 and Powder 6, respectively. FIG. 5 shows X-ray diffraction charts of powders 1 and 5, and FIG. 6 shows X-ray diffraction charts of powders 3 and 6. As described above, the sharp diffraction peaks in the diffraction charts of Powder 1 and Powder 3 are peaks attributable to the crystal structure of NiCuZn particles or MnZn particles. In the diffraction charts of Powder 5 and Powder 6 which were subjected to the above-mentioned acid treatment, sharp diffraction peaks were observed, and no change was observed even after the above-mentioned acid treatment.
[0110] 7 and 8 show the results of pore size distribution analysis by the BJH method. In Powders 5 and 6 that had been subjected to the acid treatment, in addition to the first pores originating from the tube pores of the nanotube particles and the second pores corresponding to the interparticle voids of the nanotube particles, it was found that pores of 8 nm or less had been formed that were not observed in the powders before the acid treatment (Powder 1 and Powder 3). Powder 7, which is obtained by calcining powder 5 at 900°C, and powder 8, which is obtained by calcining powder 6 at 900°C, also have pores of 8 nm or less. It is believed that the formation of the pores contributes to the increase in the amount of methylene blue adsorbed.
[0111] Powders 5 and 6, which were subjected to the acid treatment, and powders 7 and 8, which were further sintered at 900°C, were attracted to the neodymium magnet even in the dry state. This suggests that, like powders 5 and 6, powders 7 and 8 also contain NiCuZn particles or MnZn particles, respectively, and that there is no change in the magnetic properties associated with these particles. That is, even if the material is calcined at 900° C. after acid treatment, the pore structure and magnetism are maintained, so that a regeneration treatment by heating can be applied.
[0112] From the above results, it was confirmed that the powder containing the aluminosilicate granules in which the magnetic powder and the nanotube particles are composited is attracted to a magnet and easy to separate from solid and liquid (separation operation) even when the powder is subjected to acid treatment. It was also confirmed that the acid treatment generates pores of 8 nm or less and increases the amount of methylene blue adsorbed. Therefore, powders 5 to 8 obtained by acid treatment are powders with high adsorption capacity and easy to separate from solid and liquid (separation operation). It was also confirmed that the powder was attracted to a magnet even in a dry state, facilitating recovery operations. In other words, the powder of the present invention is a powder that can be easily separated and recovered. As described above, the powder of the present invention may be obtained by using the acid-treated metahaloysite nanotube particles obtained by performing the calcination treatment and the acid treatment in advance. The acid-treated metahaloysite nanotube particles often have pores of 8 nm or less, which is advantageous in terms of improving the adsorption ability.< / xrd>
Claims
1. A powder comprising aluminosilicate granules, The aluminosilicate granules include nanotube particles and magnetic particles; The aluminosilicate granules have pores with a pore size of more than 8 nm and not more than 200 nm.
2. The powder of claim 1 , wherein the magnetic particles are soft magnetic particles.
3. 3. The powder of claim 2, wherein the soft magnetic particles are soft ferrite particles.
4. 4. The powder according to claim 1, wherein the content of the magnetic particles is 2 to 50% by mass relative to the total mass of the aluminosilicate granules.
5. The aluminosilicate granules according to any one of claims 1 to 3, wherein the pores include first pores derived from tube pores of the nanotube-shaped particles and second pores different from the first pores.
6. The powder according to any one of claims 1 to 3, wherein the aluminosilicate granules have pores with a pore size of 8 nm or less.
7. The powder according to any one of claims 1 to 3, wherein the aluminosilicate granules have pores with a pore size of 8 nm or less and pores with a pore size of more than 8 nm and not more than 200 nm.
8. The powder according to any one of claims 1 to 3, wherein the aluminosilicate granules have pores with a pore size of more than 200 nm.
9. The powder according to any one of claims 1 to 3, wherein the aluminosilicate granules have pores with a pore size of more than 8 nm and not more than 200 nm and pores with a pore size of more than 200 nm.
10. The powder according to any one of claims 1 to 3, wherein the aluminosilicate granules have pores with a pore size of 8 nm or less, pores with a pore size of more than 8 nm and less than 200 nm, and pores with a pore size of more than 200 nm.
11. The aluminosilicate granules have first pores derived from the nanotube particles and having a pore size of more than 8 nm and not more than 200 nm, second pores different from the first pores and having a pore size of more than 8 nm and not more than 200 nm, and third pores having a pore size of 8 nm or less. The powder according to any one of claims 1 to 3.
12. The powder according to any one of claims 1 to 3, wherein the nanotube particles are nanotube aluminosilicate particles.
13. 13. The powder of claim 12, wherein the nanotubular particles comprise particles derived from halloysite nanotubes.
14. The powder according to any one of claims 1 to 3, wherein the aluminosilicate granules have an average particle size of 0.5 to 200 µm.
15. The method for producing the powder according to any one of claims 1 to 3, comprising the step of preparing the powder from a slurry containing nanotube particles and magnetic particles.
Citation Information
Patent Citations
Method for preparing magnetic halloysite molecularly imprinted polymer with specific adsorption to 2,4-dichlorophenoxyacetic acid
CN103613722A
Magnetic viscous fluid
JP2006286890A
Halloysite powder
WO2021172547A1
Halloysite powder and method for producing halloysite powder
WO2018079556A1